Influences of Social Media on Thai Usage of Undergraduate Students at Public Higher Education Institutions: A Case Study at Rajamangala University of Technology Lanna - Chiewchan, Sorasak (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The aim of this research was to study the opinions of students towards the use of Thai language in social media and the influences of social media on the use of Thai language. The sample were 384 students from 6 campuses of Rajamangala University of Technology Lanna. The instrument was a questionnaire. The data was analyzed by means of percentage, mean, standard deviation and descriptive analysis. The results showed that there was a high level of misspelled words in the use of Thai language in social media. Furthermore, the students believed that social media had influenced the use of their language in terms of slang. They indicated that it was easier to communicate using slang, or words taken from social media, among the same age interlocutors. In terms of the influences of social media on the use of Thai language, the results showed that social media had influenced the students’ writing and speaking ability at a high level. They employed misspelled words and slang from social media to write they applied slang and transliterations to speech. The students viewed the use of Thai language in social media as temporary; that it would remain for a period of time and constantly change.